How to square the circle of voluntary participation in controlled samples? - Kampmane, Kristine; van Staden, Surette; Ozola, Antra (Frontiers in Education, 2025)
Large-scale international education studies rely on controlled sampling designs and required response rates to ensure reliable and valid data. However, participant refusal threatens data quality. This study investigates factors that facilitate or discourage respondent participation in such surveys. A mixed-methods design was applied to the OECD TALIS 2024 Latvian dataset. The sample included schools, principals, study coordinators, and teachers. Quantitative analysis explored correlations between participation patterns and response behavior, while qualitative interviews with principals and coordinators provided deeper insights. Correlation analysis revealed that voluntary participation was strongly associated with early survey completion. When teachers completed the survey simultaneously during meetings, refusal rates fell below 1%. Most coordinators (79%) noted survey overload, and 73% suggested financial incentives for teachers. In contrast, only 30% of non-participating teachers considered payment motivating. Teachers emphasized that desirable survey features included relevance to work, completion during working hours, mobile compatibility, and accessible links. Across groups, brevity (≤10 minutes) and clarity were the most valued qualities. Principals highlighted openness to surveys when they were purposeful, relevant, aligned with school goals, and offered meaningful feedback. Findings show that participation in large-scale surveys can be enhanced through organizational support, relevance, brevity, and convenient formats, while monetary incentives appear less influential for teachers. Coordinators and principals stress the importance of purposeful design and clear benefits to respondents, suggesting strategies to reduce non-response and improve data quality in future studies.